THE RELATIONSHIP OF BIG FIVE PERSONALITY WITH BURNOUT IN MTsN HONORARY TEACHER - Mela, Mardya; Rinaldi (Causalita, 2024)
Jobs that are vulnerable to burnout are jobs that provide services directly to people. One of the jobs in the field of community service is teacher. Burnout is a state of tiredness and frustration caused by the pressure of work and hampered desires which results in a decline in physical condition, emotional exhaustion and prolonged mental fatigue. Research was conducted to determine the relationship between personality types, especially using the big five personality theory, with burnout in MTsN honorary teachers. The approach in this research uses a quantitative approach with two scales, namely the mask burnout inventory (MBI) scale and the big five inventory (BFI) scale. The sample in the research was 127 honorary teachers with a sampling technique using total sampling. Data was collected using questionnaires directly and online (Google from). This research was analyzed using multiple linear regression analysis. The results of this research are that there is a joint relationship between the big five personalities and burnout in honorary teachers based on the results of the F test with a significance level of <0.05, namely 0.000 with a fairly strong correlation of 0.570.